SOSIALISASI PEMBERDAYAAN LANSIA DALAM UPAYA MEWUJUDKAN LANSIA TANGGUH: SOCIALIZATION OF ELDERLY EMPOWERMENT IN THE EFFORT TO REALIZE RESILIENT ELDERLY - Abu Bakar; Hardiyanti (Jurnal Pengabdian Masyarakat Kesosi, 2021)
With the empowerment of the elderly in terms of posyandu aspects for the elderly, it is hoped that the elderly will be healthy, independent, qualified and productive. In line with that, the elderly do not feel burdened and must be able to know how to interpret the elderly from burdens to assets. The objectives of this activity include: 1) Providing motivation to partner communities, especially the elderly posyandu in increasing care for the elderly, 2) The ability and success of partner communities depends on family participation in caring for and handling family members, 3) The outputs of this activity are in the form of increasing the knowledge of families and the elderly about efforts to empower themselves, 4) This activity is expected to create a good synergy between health facilities, both puskesmas and posyandu for the elderly in improving the health status and independence of the elderly. Due to the current pandemic conditions, this activity was carried out online using a zoom meeting. The number of participants who were successfully recorded was based on the attendance list of 20 people. The activity of providing material lasted for approximately 50 minutes and at the end of the session the presenters gave the opportunity for participants to ask questions related to the material that had been delivered